Discordant twins as a tool to unravel the aetiology of bipolar disorder. (June 2014) - Fagnani, C.; Bellani, M.; Soares, J. C.; Stazi, M. A.; Brambilla, P.
<x content-type="archive" xml:space="preserve">Abstract</x> This editorial focuses on discordant twins as a valuable epidemiological design for psychiatric aetiological research. First, we summarise the advantages and strengths of this design over the classical matched case-control study. Then, we draw attention to the use of this method in bipolar disorder, revising previous discordant-twin studies. A future greater use of discordant twins is desirable to gain further relevant insights in the aetiology of bipolar disorder.